Dielectrically Modulated Single Schottky Barrier and Electrostatically Doped Drain Based FET for Biosensing Applications - Faisal Bashir; Furqan Zahoor; Haider Abbas; Ali Alzahrani; Mehwish Hanif (IEEE Access)
In this work, we propose a novel Gate and Drain Engineered Schottky Barrier (SB) FET (GDE-SBFET) for biosensing application with significant sensitivity improvement. Two different gate materials are employed by the proposed SB device having work functions of 3.9 eV (Al) and 4.72 eV (Cu) and electrostatically doped drain (work function of 3.9 eV). Etching out the oxide on both sides of the gate creates a nano-gap cavity that is used to detect the biomolecule. The biomolecule electrical characteristics such as charge density and dielectric constant can modify the SB on either side of the gate, which can alter the device‘s driving current. The Drain Current sensitivity ( $S_{drain}$ ) parameter are extensively analyzed at $V_{DS} = V_{GS} = 0.5$ V and a comparison between state of the art devices and conventional devices has been carried out. From the obtained results, it can be concluded that proposed device sensitivity is much superior for negatively charged and neutral biomolecules (maximum of 460 for biomolecules with negative charge, maximum of 128 for neutral biomolecule and maximum of 35 for positively charged biomolecules, at K = 12). These are the highest values of sensitivity observed for SB-FETs.